Recent estimate of Asian elephants in Borneo reveals a smaller population. Issue 2 (14th February 2022) - Cheah, Cheryl; Yoganand, K.
Abstract : Asian elephants occurring in northern Borneo form a geographically isolated and genetically distinct population. Of this, the subpopulation of Central Sabah holds the greatest opportunity for long‐term survival, due to a relatively large population size and occurrence over a vast, contiguous and protected habitat. We surveyed this subpopulation in 2015 using advanced methods to obtain a population size estimate. We used the distance‐sampling framework and laid out transects following a stratified random design for counting elephant dung piles; measured dung decay following the 'retrospective' method; and used Bayesian analysis to estimate dung decay rate and dung pile density. Thus, we estimated a posterior mean dung decay rate of 212 days (95% BCI: 133–319), an overall elephant density of 0.07 per km 2 (95% BCI: 0.03–0.11) and a population size of 387 elephants (95% BCI: 169–621). These estimates were far lower than the population size of 1132 individuals and density of 1.18 per km 2 estimated in 2008. It is unlikely that there has been a steep population decline, as there were no drastic land‐use changes between 2008 and 2015, nor were there other identifiable causes for a population decline. Therefore, it appears that the methodological and analytical flaws in the previous estimate are the most plausible reason for this observed difference. Given that the new estimate suggests a much smaller population, it is prudent and precautionary to use the new estimate as the basis for all policy decisions and conservation actions for elephants in Sabah. Abstract :